Evolution strategy of 5G network based on cloud-native computing - Jian SU (Dianxin kexue)
Cloud-native computing which is from IT domain covers a range of paths and methods that apply to different industries and also meet the needs of business diversity.Based on the 5G service-based architecture,advantages and challenges of introducing cloud-native computing into telecommunication networks were analyzed,cloud-native computing design,deployment and operation methods for telecommunication networks were introduced,the common principles of cloud-native computing that can be adopted by communications service providers were discussed,in order to promote the transformation of traditional telecommunication networks into 5G smart networks.